Mediating Effects of Supply Chain Strategy on the Relationship of Capability on Supply Chain Performance of Manufacturing Companies - Veeraiyah, Durairaj (AeU, 2015)
This paper explored the mediation effects of supply chain strategy on the relationship between capability and integration and its impact on the organization’s supply chain performance. Previous studies established no consensus to how these dimensions were related to each other. Additionally, review of literature produced limited works of academic research originating from developing regions particularly ASEAN. Based on the development of a model in this study, a survey was conducted targeting manufacturing organizations in Malaysia and Singapore. A total of 140 companies were sampled and data were analysed using the step-wise multiple regression analysis. The results showed that supply chain strategy mediates the organization’s internal and external integration with customers with relevance to supply chain performance. This finding elucidates the mediating role of strategy consistency in integration. Furthermore, operations capability and external integration with customers addressed a direct relationship with supply chain performance. These results indicate that organizations build operations capabilities and integrate externally with customers with purpose to improve their supply chain performance. From a resource-based perspective, the outcome of this research confirms that capabilities as a façade of organizational knowledge assets and processes are necessary to achieve performance improvement. This study provides critical insight to relevant stakeholders including supply chain managers on the key focus areas needed to improve supply chain performance.